Attitudes toward Lesbians, Gay Men, and their rights in a sample of ecuadorian cisgender men and women - Hermosa-Bosano, Carlos (2021)
Since 1997, Ecuador has undergone a series of changes to ensure family rights to sexual minorities. However, there is still limited research regarding attitudes toward them. This study focused on the attitudes toward lesbians (L), gay men (G), and their rights. A sample of 318 cisgender Ecuadorians who responded to an online survey was recruited. Analyses indicated that men, heterosexuals, who practice their religion, attend more frequently to religious services, and identify as conservative showed higher levels of prejudice against LG as well as less support toward their rights. Further, participants who did not have LG acquaintances, friends, family members, and those who did not know any LG parented family showed less support toward these populations. Multiple regression analyses indicated that believing that a person’s sexual orientation is learned significantly predicted the attitudes measured in our study. Implications of these findings to help reduce prejudice against LG individuals are discussed. [ABSTRACT FROM AUTHOR] Copyright of Journal of Homosexuality is the property of Taylor & Francis Ltd and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission. However, users may print, download, or email articles for individual use. This abstract may be abridged. No warranty is given about the accuracy of the copy. Users should refer to the original published version of the material for the full abstract. (Copyright applies to all Abstracts.)